(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to analyze the effect of web-based interactive multimedia on students’ learning outcomes in Pancasila Education at SMP Negeri 4 Bungbulang. The research was motivated by students’ low conceptual understanding due to the dominant use of conventional lecture methods. A quantitative approach with a One-Group Pretest–Posttest design was employed. Data were collected through learning outcome tests, questionnaires, and observations, and analyzed using t-tests and effect size calculations. The results show a significant improvement in learning outcomes, with gain scores of 36.12 and 40.24 and a very large effect size (d > 5.4). The use of multimedia also produced more homogeneous scores and increased the average achievement above the minimum mastery criteria (KKM), rising from 40–46 to 76–87. These findings align with multimedia learning theory, emphasizing the contribution of text, audio, and visual elements to conceptual understanding. The study concludes that web-based interactive multimedia is effective in improving learning outcomes and student engagement, and is recommended for integration into Pancasila Education and other value-based subjects.